2009
DOI: 10.1002/gps.2360
|View full text |Cite
|
Sign up to set email alerts
|

Subjective life satisfaction and mental disorders among older adults in UAE in general population

Abstract: The strong influence of psychiatric disorders e.g., depression, anxiety, organic brain syndrome, and hypochondriasis rather than physical disorders suggests that a lack of meaning and worries are more detrimental to life satisfaction than physical frailty. The findings underscore the need to develop interventions that help older people deal more effectively with psychiatric disorders and its comorbidities. Moreover, the results suggest that providing family support, by not allowing older adults to live alone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
36
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 34 publications
10
36
1
Order By: Relevance
“…Older adults with higher levels of financial strain in the present study reported a lower level of satisfaction with life, a finding that is consistent with previous crosssectional and longitudinal studies (Liet al, 2013;Zhang & Liu, 2007) and western studies (Bishop et al, 2003;Katz, 2009). Consistent with other studies (Ghubach et al, 2010;Mel endez et al, 2009;N ı Mhaol ain et al, 2012), we found that older adults with more depressive symptoms were more likely to report being unsatisfied with life. Consistent with previous findings (Cheng & Chan, 2006;Huang, 2012;Silverstein et al, 2006;Yeung & Fung, 2007), we found that family relationships are important to older adults in the Chinese society.…”
Section: Discussion and Implications Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Older adults with higher levels of financial strain in the present study reported a lower level of satisfaction with life, a finding that is consistent with previous crosssectional and longitudinal studies (Liet al, 2013;Zhang & Liu, 2007) and western studies (Bishop et al, 2003;Katz, 2009). Consistent with other studies (Ghubach et al, 2010;Mel endez et al, 2009;N ı Mhaol ain et al, 2012), we found that older adults with more depressive symptoms were more likely to report being unsatisfied with life. Consistent with previous findings (Cheng & Chan, 2006;Huang, 2012;Silverstein et al, 2006;Yeung & Fung, 2007), we found that family relationships are important to older adults in the Chinese society.…”
Section: Discussion and Implications Discussionsupporting
confidence: 95%
“…Having a depressive disorder is more strongly associated with less life satisfaction than physical frailty (Ghubach et al, 2010;Mel endez et al, 2009;N ı Mhaol ain et al, 2012). Family support is positively associated with life satisfaction among older adults (Kim & Sok, 2012).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…, Ghubach et al . ). To the best of our knowledge, there have been no previous studies in which life dissatisfaction has concurrently and longitudinally been investigated with respect to separate RAND dimensions.…”
Section: Discussionmentioning
confidence: 97%
“…Public health policies are concerned with how to keep older people living independently with a good quality of life (Jeste et al 2013), which often worsens in old age: the oldest have more complaints than the youngest (Thomé et al 2004); pain negatively affects their quality of life (Jakobsson et al 2004); oral diseases are a public health problem, frequently neglected in older people (Fuentes-García et al 2012) who experience more chronic diseases of greater severity, take more medications and are hospitalized for longer periods than younger people (Pascucci et al 2012). Aging males, in particular, have the risk of developing gender-specific urological diseases and may run a higher risk of cardiovascular complications than women (Lunenfeld 2002).…”
Section: Introductionmentioning
confidence: 99%